Employees’ Empowerment and Its Role in Achieving Strategic Success: A Practical Study on Jordanian Insurance Companies - Abuzaid, Ahmad (Jordan Journal of Business Administration, 2018)
The purpose of this study is to identify the role of employees’ empowerment in achieving strategic success of 20 Jordanian insurance companies listed in Amman Stock Exchange. The sample of the study included all the study population. The sample included 306 employees working at the target companies. In order to achieve the study objectives, the researcher designed a questionnaire to collect the required data. To test the study hypotheses, multiple regression analysis was used. The study results indicated that there is a strong relationship between employees’ empowerment and strategic success. Additionally, the study results showed that the delegation of authority, participation and work environment, as dimensions of employees’ empowerment, have a positive impact on strategic success. Based on these results, the researcher recommended that organizations should adopt an employee empowerment approach in order to achieve strategic success and ensure the success of the empowerment process by creating a supportive work environment that involves training, exchange of information, open communication and encouraging employees to introduce their creative ideas related to the development of work. In addition, the study also recommended delegating employees’ adequate authority to carry out their duties in an effective way and involving them in the process of decision making and setting organizational goals.